MOSQUE WITHOUT DOME: CONSERVING TRADITIONAL-DESIGNED MOSQUE IN MELAKA, MALAYSIA - M. Zailan Sulieman, Roslan B. Thalib (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2011)
Jasin is one of the area in the state of Malacca in Malaysia, known for its long winding history. Located in the middle seat of government of the Empire of the famous Melaka Sultanate, Jasin district does have a number of quality historic buildings. One of the old buildings found in one the villages located quite close to the town of Jasin is the unique domeless Air Barok Village Mosque. Its location is situated along the main road, easy to reach. In a study stated in this paper, it Â shows how the unique architecture of this mosque of Air Baroque Village can be appreciated. This paper presents a study of the design elements and architectural features that are unique to the mosque around this region. This paper stated on the approach in creating this structure is different compared to most of the existing mosque currently and previously being built around the state. The concept of neo-archipelago idea to have the Chinese Buddha features in a Muslim mosque was unique found on this religious building located at the side of the world. Expectations for this study to reveal the noble efforts of the Government bodies involved in restoring old Â buildings such as this mosque can indirectly maintain the cultural arts of the local Malays who are the largest race in Malaysia. Efforts should also be given to maintain old buildings; not only religious buildings but also other building types; in the effort to ensure local arts and culture still exist and can be appreciated by future generations. Â Keywords: Traditional mosque, conservation, mosque history, Melaka mosque